Foreign Banks in Eastern Europe: Mode of Entry and Effects on Bank Interest Rates - Sophie Claeys; Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Credit markets in many Eastern European countries are now dominated by foreign-owned banks. We analyze the development for foreign ownership and its impact on lending rate in ten Eastern European countries between 1995 and 2003. Currently, the majority of loans from foreign banks is granted by acquired banks. The presence of foreign acquired banks as measured by their relative number among the banks in our dataset increased somewhat slower than that of foreign de novo banks. However, since market entry through acquisition allows acquiring a credit portfolio and a customer base, acquired banks were able to expand their market share much faster than the foreign de novo banks. Our results also show that the interest rate decreased after foreign bank entry. Moreover, while the reduction in interest rates of domestic banks is more pronounced in the case of foreign entry through a de novo investment, foreign de novo banks charge higher interest rates than foreign acquired banks.
urn:nbn:de:bvb:19-epub-13456-2
Keywords: D4; G21; 330; SME; Banking; Foreign Entry; Mode of Entry; Interest Rate